Risk pricing : using quantum electrodynamics for higher order risks - Chorafas, Dimitris N. (Harriman House, 2010)
A guide to how the financial world got risk so badly wrong - and how it might avoid doing so again. It helps to manage risk through the correct pricing of exposure embedded in financial products